2021
DOI: 10.3389/fonc.2021.645162
|View full text |Cite
|
Sign up to set email alerts
|

18F-Trifluoromethylated D-Cysteine as a Promising New PET Tracer for Glioma Imaging: Comparative Analysis With MRI and Histopathology in Orthotopic C6 Models

Abstract: Comparing MRI and histopathology, this study aims to comprehensively explore the potential application of 18F-trifluoromethylated D-cysteine (S-[18F]CF3-D-CYS) in evaluating glioma by using orthotopic C6 glioma models. Sprague–Dawley (SD) rats (n = 9) were implanted with C6 glioma cells. Tumor growth was monitored every week by multiparameter MRI [including dynamic contrast-enhanced MRI (DCE-MRI)], [18F]FDG, S-[18F]CF3-D-CYS, and [18F]FDOPA PET imaging. Repeated scans of the same rat with the two or three [18F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Furthermore, D-AAs derived positron emission tomography (PET) radiotracers have demonstrated promising application in clinical diagnosis, including brain tumor, brain glioma tissue, and bacterial infection, etc. [157][158][159]. It has better specificity and absorption in tumor/infected tissue, as well as outperforming its L enantiomers [157][158][159].…”
Section: Incorporating D-aas Into Drugs Afford Stronger Biostability ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, D-AAs derived positron emission tomography (PET) radiotracers have demonstrated promising application in clinical diagnosis, including brain tumor, brain glioma tissue, and bacterial infection, etc. [157][158][159]. It has better specificity and absorption in tumor/infected tissue, as well as outperforming its L enantiomers [157][158][159].…”
Section: Incorporating D-aas Into Drugs Afford Stronger Biostability ...mentioning
confidence: 99%
“…[157][158][159]. It has better specificity and absorption in tumor/infected tissue, as well as outperforming its L enantiomers [157][158][159].…”
Section: Incorporating D-aas Into Drugs Afford Stronger Biostability ...mentioning
confidence: 99%
“…In another study, Tang and coworkers further explored the potential application of [ 18 F] 17 in evaluating glioma by comparing magnetic resonance imaging (MRI) and histopathology. The results showed that, compared with [ 18 F]FDG and [ 18 F] 1 , [ 18 F] 17 had the highest TNRs in the same orthotopic C6 glioma models, suggesting that the tracer may serve as a valuable tool in the diagnosis of gliomas [ 59 ].…”
Section: Synthesis Of 18 F-labeled Aas Via [ ...mentioning
confidence: 99%
“…As displayed in Table 2, for cyclic substrates, both secondary and tertiary alkyl groups, including cycloheptyl (4), various cyclohexyls (5-7), cyclopropyls (8)(9)(10)(11), adamantly (12) all underwent the reaction system smoothly to afford the coupling products in good to excellent yields. Of them, keto (7), -MeO (9), -Cl (10), -CF 2 (11), substituents were all well tolerated, as well as substrates derived from piperidine, tetrahydropyranyl and tetrahydrofuranyl (13)(14)(15). Moreover, no obvious bias toward reaction efficiency was observed in acyclic substrates which exhibited in either secondary (16, 17), primary (18,19) or benzyl (20) structures.…”
mentioning
confidence: 97%
“…For instance, 18 F-trifluoroborate-derived tyrosine ( 18 F-FBY) has demonstrated exciting potential in clinical PET imaging. [9][10] Furthermore, both trifluoromethyl and boronic groups have been proved to be valuable functionalities in cold pharmaceuticals, [11][12] as well as in hot radiopharmaceuticals [13][14] (Figure 1a, 1 b). Interestingly, although "F&B couple" hold great promise in PET-BNCT radiotheranostics, efforts to fuse a CF 3 functionality into a boronic molecule to get fluorinated organoboronates were less devoted.…”
mentioning
confidence: 99%